Optimization of fast moving robots and implementation of I2C protocol to control electronic devices - Ribeiro, A. Fernando (2005)
This paper briefly describes the main changes in the robots from Minho Team since the last RoboCup. Work has been carried out on the robots in order to constantly improve their capabilities, based on the experiences from previous participations. The main topics to deal in this paper are related with the I2C new communications protocol recently implemented in the robots, a description of the whole electronics system based on a new diagram which contains all the devices used in the robots, the inclusion of new faster motors, a description of the robot game play strategy, some operating system remarks which are related to some requirements of our actual system, and the main conclusions related to the work carried out so far. The use of the I2C protocol forced the team to change all the electronic boards and these were completely redesigned in-house, tested and implemented on the robots.